Guide to a Comprehensive Geriatric History - Maria H. van Zuilen; Willa Xiong; Marcos Milanez; Michael Mintzer (Association of American Medical Colleges, 2013)
Abstract The purpose of this guide is to give learners an overview of the different components to consider when taking a history in an older adult. The history taking process with older adults is different from that with younger adults because the geriatric population is more likely to have multiple, often complex medical, social, economic, and psychological factors that impact functional status and quality of life. This guide is geared towards medical students but may also be helpful for residents and healthcare providers or trainees from other disciplines involved in the care of older adults. This guide can stand alone as a study or reference material for a clinical skills or medical interviewing course, but it is best paired with a practice opportunity. In our curriculum, first-year medical students use this guide to prepare for a home visit with an active community-residing older adult. The guide includes information and questions that are practical and appropriate for routine office use or in-home assessments. A separate four-page worksheet is included that lists the core elements learners should assess and some space to make notes. We have successfully used this guide to help first-year medical students prepare for a home visit with an active older adult residing in the community. After the home visit, we asked students to submit an online report using a standard history format. In prior years, we gave students a more abbreviated guide that broadly outlined the topics to ask about, but without providing an explanation or sample questions to ask. In comparison, the students who used the newer guide clearly addressed more topics. The quality of the submitted assignments improved significantly and the variability in grades is considerably less.